2019
DOI: 10.1364/oe.27.020145
|View full text |Cite
|
Sign up to set email alerts
|

High-speed double layer graphene electro-absorption modulator on SOI waveguide

Abstract: We report on a C-band double layer graphene electro-absorption modulator on a passive SOI platform showing 29GHz 3dB-bandwith and NRZ eye-diagrams extinction ratios ranging from 1.7 dB at 10 Gb/s to 1.3 dB at 50 Gb/s. Such high modulation speed is achieved thanks to the quality of the CVD pre-patterned single crystal growth and transfer on wafer method that permitted the integration of high-quality scalable graphene and low contact resistance. By demonstrating this high-speed CVD graphene EAM modulator integra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 32 publications
6
75
0
Order By: Relevance
“… 7 , 9 , 11 The ultrafast electron excitation dynamics (< 50 fs) 12 upon optical excitation, and the consequent short relaxation time, of the order of few ps, 12 enable high-speed devices. 13 Fast graphene photodetectors (GPDs) have been demonstrated, 8 , 14 19 with bandwidth > 100 GHz. 17 19 In terms of speed, such devices can compete with Ge-based PDs.…”
mentioning
confidence: 99%
“… 7 , 9 , 11 The ultrafast electron excitation dynamics (< 50 fs) 12 upon optical excitation, and the consequent short relaxation time, of the order of few ps, 12 enable high-speed devices. 13 Fast graphene photodetectors (GPDs) have been demonstrated, 8 , 14 19 with bandwidth > 100 GHz. 17 19 In terms of speed, such devices can compete with Ge-based PDs.…”
mentioning
confidence: 99%
“…Moreover, the dielectric permittivity of hBN is rather low compared to existing high-κ dielectrics 29 , with a value close to that of SiO 2 (ϵ r ∼ 4). This low dielectric constant and reduced breakdown voltage (see section V in SI) compromises not only the power consumption and the ability to reach high modulation efficiencies at reasonably low drive voltages but also limits the IL and the ER of the modulators 1,9 . We thus integrate HfO 2 , a high-κ dielectric material, within the hBN-encapsulated graphene electrodes (see the sketch in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…high-speed 8,9 , relatively high modulation efficiencies 10 and temperature stability 8 . These devices are all based on CMOS compatible materials 7,[10][11][12][13] , where CMOS design and fabrication techniques can be further leveraged to decrease costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the electro-absorption modulation, it utilizes the change in the optical absorption of graphene induced by the shift of Fermi level produced by electrical gating [40]. Giambra et al [41] demonstrated a broadband electro-absorption modulator with 29 GHz bandwidth by integrating the dual-layer graphene capacitor on the passive SOI waveguide. Besides the dual-layer graphene capacitor, Shu et al [42], Hu et al [43], and Sorianello et al [44] demonstrated the graphene-oxide-silicon capacitor-based waveguide-integrated modulators, in which the gate voltage is applied through the intentionally doped silicon waveguide.…”
Section: Waveguide-integrated Graphene Photonic Devices For Communicamentioning
confidence: 99%